The Relationship Between Self-Regulated Learning and the Activeness of Upper-Grade Students at SD Inpres 12/79 Walenreng 1, Cina District, Bone Regency - Winny Ulama Putri; Muhammad Idris Jafar; Abd. Kadir A (Journal of Primary Education Innovation and Research, 2025)
This study is a symmetrical correlational study using a quantitative approach, which aims to determine whether there is a significant relationship between self-regulated learning and the activeness of upper-grade students. The population in this study consisted of all upper-grade students at SD Inpres 12/79 Walenreng 1, with saturated sampling used as the sampling technique. The sample in this study consisted of 60 students. Data were collected using a questionnaire. The data analysis techniques used were descriptive statistical analysis and inferential statistical analysis. Based on the results of the descriptive statistical analysis, self-regulated learning obtained a mean score of 58.37, which was categorized as moderate, while student activeness obtained a mean score of 58.42, which was also categorized as moderate. The results of inferential statistics showed that r-count ≥ r-table (0.424 ≥ 0.254) at a significance level of 5%. Thus, H1 was accepted and H0 was rejected. Based on these findings, it can be concluded that there is a significant relationship between self-regulated learning and the activeness of upper-grade students at SD Inpres 12/79 Walenreng 1, Cina District, Bone Regency, which is classified as moderate within the 0.40–0.599 category